KEMAMPUAN NASIONAL DALAM PENGEMBANGAN PESAWAT TERBANG TANPA AWAK KELAS MEDIUM ALTITUDE LONG ENDURANCE - Agus Bayu Utama; Siswo Hadi Sumantri; Romie Oktovianus Bura; Gita Amperiawan (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The Indonesian Ministry of Defense has established a policy for the use of unmanned aircraftÂ in a variety of military and non-military operations carried out by its troops. The defense industry's independence is also encouraged to develop unmanned aircraft class medium altitude long endurance (MALE). This study was conducted to analyze national capabilities in the development of unmanned aircraft in the MALE class. The research method used is qualitative with a survey to unmanned aircaft developer and user communities. Primary data is processed using Excel software and displayed in the form of tables and graphs. The result: Indonesia has already the capability to design, manufacture, and use class 1 (small) of unmanned aircfrat products, namely the maximum take-off weight (MTOW) of aircraft weighing less than 150 kg but in the development class 3 (large) of unmanned aircraft, namely the MTOW of aircraft above 600 kg and operating altitude < 13,716 km, Indonesia is only able to make designs and test models in the wind tunnel, MALE Elang Hitam (EH) development through a consortium that began in 2017 was the first activity and become a means of increasing national capacity.